Behavior Guidance Techniques in Pediatric Dentistry: An Update - Güngör, Erva; Karamüftüoğlu, Nevra (Turkey Health Literacy Journal, 2025)
Dental anxiety, fear, and phobia are common psychological conditions encountered in pediatric dentistry, often leading to treatment compliance difficulties and adverse oral health outcomes. The development of these conditions is influenced by children’s previous experiences, parental attitudes, and environmental factors. To address these challenges, various behavior management techniques have been developed in pediatric dentistry. These techniques include communicative approaches, reinforcement methods, distraction, and desensitization strategies, with their effectiveness supported by the literature. However, the advantages, limitations, and parental acceptance of these methods may vary.The aim of this review is to summarize current behavior management techniques in pediatric dentistry, discuss their effectiveness and limitations, and provide practical recommendations for clinical applications. In conclusion, individualized technique selection and consideration of parental involvement are critical for treatment success and for fostering positive dental attitudes in children.
Keywords: Pediatric Dentistry; Behavior Management; Dental Anxiety; Dental Fear; Dental Phobia